Weight gain stopping/switch rules for antiretroviral clinical trials. (15th December 2021) - Venter, W.D. Francois; Sokhela, Simiso; Calmy, Alexandra; Mkhondwane, Luckyboy; Bosch, Bronwyn; Chandiwana, Nomathemba; Hill, Andrew; Sekwese, Kenly; Mashabane, Nkuli; Pozniak, Anton; Khoo, Saye; Ali, Mohammed; et al.
Abstract : Obesity develops in a substantial number of people initiating and maintaining modern antiretroviral therapy. The comorbidities associated with obesity make significant weight gain and metabolic changes a major consideration in clinical trials studying different regimens' potency and safety. It is as yet unclear what role individual antiretrovirals or classes play in weight gain but the issue is a complex one for clinical trial design, especially when deciding when "too much" weight has been gained, in a context where we do not yet know if switching to alternative regimens will slow, halt or reverse weight gain or metabolic changes. In addition, clinician and trial participant opinion on acceptable weight gain may differ. We offer preliminary guidance for discussion for future antiretroviral clinical trial design.